Offering Acupuncture as an Adjunct for Tobacco Cessation: A Community Clinic Experience. Issue 5 (September 2013) - Chang, Emiley; Fung, Lei-Chun; Li, Chin-Shang; Lin, Tzu-Chun; Tam, Leonard; Tang, Carrie; Tong, Elisa K.
Disparities in smoking rates remain prominent within Asian Americans. Medical pluralism and cultural tailoring may enhance Asian Americans engaging with tobacco cessation assistance. We conducted a retrospective analysis of a community clinic's smoking cessation program targeting a Chinese population that offered acupuncture, nicotine replacement therapy (NRT), and counseling from 2007 to 2010. Most participants used acupuncture, with about half choosing acupuncture and NRT, followed by more than 40% choosing acupuncture only; few chose NRT only. Tobacco cessation rates at 6 months were relatively high for the acupuncture + NRT group and only acupuncture group (37.7% vs. 28.9%). In comparing tobacco reduction >50% from baseline with an expanded only NRT group, the acupuncture + NRT group had a higher odds ratio than the only acupuncture group, which had a lower odds ratio. Our evaluation of this real-world community program offering acupuncture as a cultural adjunct to a tobacco cessation program suggests that acupuncture might help with engagement by Chinese American male smokers into a tobacco cessation program that offers counseling and NRT. Future larger studies should further evaluate the efficacy of offering acupuncture in combination with NRT on the outcomes of cessation and reduction.